2013
DOI: 10.1159/000346691
|View full text |Cite
|
Sign up to set email alerts
|

Review of 36,537 Patient Records for Tooth Health and Longevity of Dental Restorations

Abstract: To develop an automatic system for utilizing electronic dental records, a data mining system to extract the diagnostic and treatment codes from the records for an intermediate file and automatic drawing of Kaplan-Meier-type survival curves was first created. Then this intermediate file was analyzed with SAS software for the scientific determination of Kaplan-Meier survival of tooth/surface-specific healthy time and survival of restorations in each permanent tooth, health center, and age cohort and also combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…[4][5][6] Failures after this period have been associated with secondary caries, marginal deficiencies, degradation/wear, fracture, or loss of anatomic form. 5,[7][8][9][10][11][12][13][14][15][16] The replacement of failed restorations is the most common treatment in dentistry 10 years after initial placement, and long-term studies have shown that when failure takes place it typically happens within the first 24 months. 17 Dentists frequently replace restorations that could be treated in a more conservative manner.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Failures after this period have been associated with secondary caries, marginal deficiencies, degradation/wear, fracture, or loss of anatomic form. 5,[7][8][9][10][11][12][13][14][15][16] The replacement of failed restorations is the most common treatment in dentistry 10 years after initial placement, and long-term studies have shown that when failure takes place it typically happens within the first 24 months. 17 Dentists frequently replace restorations that could be treated in a more conservative manner.…”
Section: Introductionmentioning
confidence: 99%
“…Since a class II replaces the marginal ridge, which the TR attempts to protect, it may be possible that the strength and longevity of modern composites may have reduced the need for conservative TR. A recent study found that the median lifespan of all dental restorations was 11.7 years with a large amount of variation between different health centers and different teeth in the study. More research is necessary to accurately determine the longevity of TR, and those findings must be weighed against each clinical case in the decision to choose TR as the treatment of choice.…”
Section: Discussionmentioning
confidence: 85%
“…The first permanent molar has the shortest caries-free survival under the age of 8 years [ 10 ]. It also represents the most caries prone tooth in children older than 11 years [ 11 ]. In addition to this, first molars can suffer from developmental enamel hypomineralisation of unknown aetiology often affecting permanent incisors.…”
Section: Discussionmentioning
confidence: 99%